Quantitative Analysis of Drainage Basin Characteristics - Rastogi, R.A.; Sharma, T. (Journal of Soil and Water Conservation, 2022)
It has been recognised by hydrologists and geomorphologists that certain relations must exist between runoff characteristics and topographic or gemorphic characteristics of drainage basin systems. Various important hydrologic phenomenon can be correlated with the physiographic characteristics of drainage basins such as size, shape, slope of drainage area, drainage density, size and length of tributaries etc. Studies conducted at Columbia University by Strahler (1967) and Iowa State University by Gray (1961) show interrelationships of watershed geometry variables pertinent to defining the unit graph, a measure of the rate water is collected at a given point in a watershed. Several other studies reported by Schumm (1956), Leopold and Miller (196) and Hack 1957 ) define these variables for certain watersheds.